Disinfectants and devices for surface and air disinfection in dental offices - Matys, Jacek; Grzech-Leśniak, Kinga; Dominiak, Marzena (Journal of Stomatology, 2020)
SARS-CoV-2 virus pandemic that caused COVID-19 disease has altered the entire dental community. Because of COVID-19 pandemic, almost all dental practices in Poland were closed for few weeks and later, some of the offices were treating emergency patients only. Medical market offers a variety of different disinfection products for dental offices; however, not all of them significantly eradicate the virus. The present overview of various disinfectants and disinfection devices/methods showed the most substantially beneficial for application in dental clinics. Considering the advantages and disadvantages of the devices described in this paper, the highest level of air disinfection present plasma devices, which work without any additional filters that need to be replaced. In turn, fumigators with hydrogen peroxide for spraying provide the highest bactericidal, virucidal, and fungicidal effects on surfaces in the dental office (walls, medical devices, cabinets, countertops, etc.), with minimal side effects and short time needed to re-enter the office after disinfection. It should be remembered that fumigators require hydrogen peroxide plasma or chemically stabilized hydrogen peroxide to operate with high efficiency at low solution percentage. Correct application of a disinfectant with suitable method for its application improves the effectiveness of disinfection and reduces the risk of infection of staff and patients.